234PImplementation of mainstream BRCA testing in epithelial ovarian cancer in a tertiary centre. (24th November 2019) - Wong, E; Chrystal, K; Wilson, M; Wilson, L; Forgeng, C; Gamet, K; Stephens, R
Abstract: Background: The literature reports that a minority of women with epithelial ovarian cancer (EOC) are referred for germline BRCA testing despite implications for treatment and cancer prevention. Mainstream testing is BRCA testing undertaken by the Medical Oncology service, rather than clinical genetics; and it was introduced at Auckland Hospital in 2017. This study assessed whether the implementation of mainstreaming increased the uptake and timeliness of BRCA testing in a multi-cultural tertiary centre. Methods: A retrospective analysis of women with high grade non-mucinous EOC attending Medical Oncology clinic was performed prior to and after the introduction of mainstream testing. Eligibility for BRCA testing included those with the above diagnosis ≤ 70 years (tested by Medical Oncology after mainstreaming introduced) and patients > 70 years with a personal and/or relevant family history (tested by genetics). The primary outcome was the proportion of eligible patients who underwent BRCA testing. A secondary outcome was the time to the availability of the BRCA test result. Results: The proportion of eligible women tested for germline BRCA mutations significantly increased (Table). The improvement was due to increased testing via mainstreaming; there was no change in the proportion of women tested through the Genetics service. Efficiency of testing also improved; the median time from Genetics referral to an available BRCA result was 146 days (range 37 to 1599 days) and from Medical Oncology assessment to BRCA test result 64 days (range 34 to 471 days) before and after mainstreaming respectively. Overall, 14.9% of women had germline BRCA 1 or 2 mutations. Conclusions: Mainstream testing for germline BRCA mutations improved quality – access and timeliness – for women with EOC. Efficiency of testing will have important therapeutic implications. Legal entity responsible for the study: Auckland District Health Board. Funding: Auckland District Health Board. Disclosure: All authors have declared no conflicts of interest.